How is intrinsic motivation utilized in incentive systems and management practices? : a case study in Finnish telecommunications provider - Haavisto, Ville (2024)
In today’s market, an organization’s ability to attract and retain skilled employees is becoming an increasingly valuable competitive advantage. As monetary compensation in competing organizations tends to be on a similar level, intrinsic factors like well-being and happiness at work have become crucial when employees consider where they want to work. Despite this, an organization’s ability to provide psychological well-being and happiness has seen little study compared to extrinsic reward systems. This study aims to recognize how organizations utilize intrinsic motivation through their reward systems and management practices. This is done in two parts: first, the organization’s efforts to increase intrinsic motivation are discussed with their representative. Afterwards, the effects of these efforts are discussed with employees. The discussions are based on self-determination theory’s three psychological needs of competence, autonomy and relatedness. For practicality, topics were centered around six types of rewards – four intrinsic (sense of meaningfulness, autonomy, sense of competence and sense of progress) and two extrinsic ones (tangible and verbal rewards). This research used a qualitative case study method and was conducted at Elisa, a Finnish telecommunications provider. The data was gathered using semi-structured thematic interviews, one with Elisa’s representative and four with store managers. Results show that Elisa’s efforts to enhance intrinsic motivation were moderately successful. The biggest contributor towards increased intrinsic motivation was the managerial autonomy support Elisa provided, which not only boosted perceived autonomy but also led to an enhanced sense of self-competence as it allowed store managers to independently face and overcome daily challenges at their work. Tangible rewards and performance measurement systems, in turn, received criticism and had neutral and negative implications on intrinsic motivation.